Finance and Development, March 1979. (Finance and Development; Finance and Development ;, 1979)
This paper focuses on the Fourth Annual Review of Project Performance Audit Results. The paper highlights that the purpose of the Review is to provide lessons of experience relevant to the World Bank's current practices that can be applied to the design and implementation of future projects. The projects encompassed by this latest Review include: 38 in transportation, 20 in the field of public utilities, 17 in agriculture, 16 in development finance companies and industry, 11 in education, and 7 'nonproject' or program loans.